The Sustainability of Government Deficits Old Vs. New Europe - Plocek, Tomáš (2011)
This work analyses fiscal sustainability and position of old and new members of EU and offers some fiscal policy implications to deal with debt reduction in the aftermath of the current fiscal crisis in the EU. Fiscal policy of Old European countries is different from fiscal policy of the new members. Due to different historical development New European members have lower debt and lower GDP per capita. Many policymakers in New Europe tried to increase GDP of their countries by generating government deficits. On the other hand Old European countries are already having large debts and current fiscal crisis is one result of this fact. The recent fiscal crisis in Europe raised the question what is sustainable fiscal policy and how to achieve it. Sustainability of the policy can be divided into three groups: short term, medium term, and long term. In short term, fiscal policy is sustainable, when government is able to issue and sell government bonds. Otherwise it defaults. In medium term, fiscal policy is sustainable when debt to GDP ratio is constant or decreasing. Situation in long term is very similar to situation in medium term. The difference is in time. Long term fiscal policy is sustainable if debt to GDP ratio converges to some finite number. All the definitions are problematic and problem arises basically from fact that variables that are part of the definitions are volatile. Fiscal policy that might seem to be sustainable in times of economic expansion may become unsustainable even in short time. Exactly this thing happened in Ireland. Ireland shows another problem of sustainability definitions. The problem is that private debt can increase public debt and even threaten its sustainability. Many countries were saving their financial sector which was very expensive and this practice is increased the debt in those countries very fast. Probably the most important indicator of fiscal sustainability is interest rate on government bonds.